Experimental scale model study on explosion of clean refrigerant leaked in an underground plant room. (August 2018) - Gao, Z.M.; Gao, Y.; Chow, W.K.; Wan, Y.; Chow, C.L.
Highlights: Experiments on explosion of leaked propane refrigerant were performed. A model chamber with two mechanical ventilation designs in a plant room was used. Flammable gas concentrations, transient temperatures and pressures were measured. Mixing of leaked flammable refrigerant depends on mechanical ventilation design. Abstract: Several clean refrigerants widely used in new air-conditioning systems are composed of flammable propane. Leakage of the flammable refrigerant from the air-conditioning systems housed in a basement plant room would pose fire and explosion hazards. However, very few studies have been carried out to study explosion hazards of leaked clean refrigerant in underground spaces. In this paper, a model chamber with two common mechanical ventilation designs in basement plant room was used to study experimentally the hazards. Clean flammable refrigerant was discharged to the model chamber to a concentration level less than the lower flammability limit. Four sets of tests with different ventilation conditions were carried. Concentrations of the leaked refrigerant at different positions in the chamber under different ventilation conditions were measured. Explosion of leaked gas was triggered by ignition. After ignition the transient gas temperature and pressure inside the model were recorded. Results indicate that mixing of leaked flammable refrigerant, and hence the concentrations of the leaked gas, depends on the mechanical ventilation design in the chamber. Improper ventilation provision would result in high refrigerant-to-air mixing ratio at some positions, even though the designed leaked refrigerant concentration is less than the lower flammable limit calculated from a well-mixing model. The results of the present study would contribute to better understanding of explosion hazards due to leakage of flammable refrigerant in green air-conditioning and refrigeration system in basement plant room or similar enclosures.